Effects of different soil management styles and cropping practices on the yield and quality of fava bean (Vicia faba L.) - Somayeh Karami (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2023)
This research aimed to determine the effects of various soil tillage techniques and the use of organic and chemical fertilizers on the overall yield and quality of fava beans. The study emphasized the significance of fertilizer types and their interaction with soil tillage methods. Although the quantity of grains per pod was notably influenced by the choice of fertilizers, the impact of soil tillage alone was found to be insignificant. Moreover, this study demonstrated that the yield index of fava beans was significantly influenced by fertilizer sources, emphasizing the importance of proper nitrogen managements. These findings provide valuable insights for enhancing crop production and quality through optimized soil tillage practices and the use of organic and chemical fertilizers. Through an examination of both the measurable and qualitative elements of fava bean cultivation, this study offers valuable knowledge on how to optimize the application of nitrogen fertilizers and effectively utilize mycorrhizal inoculation to improve grain yield and seed quality. These findings have implications for sustainable agriculture practices and guide farmers and researchers in making informed decisions regarding soil management strategies in fava bean cultivation.